Miltefosine Administration in Cats with Refractory Sporotrichosis - Silva, Francina dos Santos; Cunha, Simone Carvalho dos Santos; Baptista, Andrea Regina de Souza; Baptista, Vivian dos Santos; Silva, Kássia Valéria Gomes Coelho da; Coêlho, Thais Fernanda Queiroz; Ferreira, Ana Maria Reis (Acta Scientiae Veterinariae, 2018)
Background: Sporotrichosis is a zoonosis caused by fungi of the Sporothrix schenckii complex. Cats have important zoonotic potential due to the high parasite load found in the cutaneous lesions. Refractory cases to antifungal therapy are increasing, becoming a public health problem. Miltefosine is a drug with high in vitro activity against Sporothrix brasiliensis. However, this efficacy has not been confirmed in vivo yet and administration has not been studied in the feline species. This study aimed to evaluate the effectiveness and safety of miltefosine administration in cats with resistant sporotrichosis. Materials, Methods & Results: Ten cats with refractory sporotrichosis were included in this study. Inclusion criteria were previous diagnosis for sporotrichosis associated with therapy with oral antifungals (itraconazole and/or potassium iodide) for more than one year, followed by one of these conditions: incomplete clinical remission, worsening of disease during treatment or recurrence after conventional treatment. Cats underwent clinical and dermatological examinations. Data on lifestyle and previous treatments were provided by the owners. Fungal culture and histochemical techniques were performed in all cats before miltefosine treatment. Blood samples were collected before and during the study for laboratory tests, such as blood count, blood urea nitrogen (BUN), serum creatinine, alanine aminotransferase (ALT) and alkaline phosphatase, as well as serology for Feline Immunodeficiency (FIV) and Feline Leukemia (FeLV). Miltefosine was prescribed at a dosage of 2 mg/kg orally every 24 h. The animals were monitored by phone during the whole process and reassessed on days 0, 15, 30 and 45 of the treatment. Out of 10 cats, lesions were present on the nose in nine, ears in four, periocular areas in one and limbs in four. One cat received treatment for 45 days, six for 30 days, one for 21 days, one for 15 days and one for 3 days. One cat showed no response to the treatment and nine showed disease progression. Hyporexia and weight loss were the most frequent clinical signs related to miltefosine treatment, followed by sialorrhea, vomiting and diarrhea. Few adverse effects on hematology and biochemistry (mainly renal and hepatic parameters) were observed during the study. Hematocrit decrease was observed in four animals. However, only one cat had hematocrit decrease below normal values (anemia), which was already present before miltefosine administration. Other cats had a decrease of five points. Three cats showed elevation in leucometria and four in plasma protein. In relation to renal and hepatic biochemistry, one animal showed a BUN increase and another one showed a transient increase in ALT. Two animals started the treatment with increased ALT but had no problems during the study and values decreased even during the miltefosine administration. Discussion: Although two cats showed sialorrhea, most owners did not report difficulty in administering the drug orally, representing an advantage of this medication. Weight loss, secondary to gastrointestinal changes, was the most clinically relevant alteration. The most frequent hematological alteration was hematocrit decrease and only the animal that started the study with 20% hematocrit ended the study with anemia. Renal and hepatic parameters were not significant in the cats of this study. Miltefosine did not lead to sporotrichosis remission in this small population of cats, which reveals that, despite its in vitro efficacy against Sporothrix spp., the drug is not effective in vivo in the feline species. Further studies are needed to investigate the efficacy of this drug in a larger number of cats, and possible reasons for its in vivo ineffectiveness.